Optimal the ex-situ biogas biological upgrading to biomethane and its combined application with the anaerobic digestion stage. Issue 17 (2nd September 2021) - Tang, Qing; Xu, Jin; Liu, Ziyi; Huang, Zhenxing; Zhao, Mingxing; Shi, Wansheng; Ruan, Wenquan
ABSTRACT: Biomethane upgraded from biogas had been proven as a potential renewable energy. Utilizing the metabolic activity of enriched hydrogenotrophic methanogens was regarded as a new way to upgrade biogas. The optimal reaction pH and mixed gas (H2 and CO2 ) injection time for enriching hydrogenotrophic methanogens were identified, and the performance of upgrading raw biogas produced from food wastes anaerobic digestion was assessed in this study. In the optimal experiment, the results showed that the maximum methane content reached 61.01% when pH was 8 and injection time was 5 min. In all groups, the concentration of acetic acid showed a trend of increasing followed by decreasing during this process. High-throughput sequencing indicated that Methanobacterium and Methanoculleus belonging to hydrogenotrophic methanogens were the dominated genus. The maximum methane content reached 91.43% in the biogas upgrading stage when it was combined with anaerobic digestion stage. At the end of the experiment, the methane content of the upgrading stage was 36.66% higher than that of the raw biogas produced from anaerobic digestion stage. Microbiological analysis showed that hydrogenotrophic methanogens were also the predominant genus.